Tata Kelola Komparatif Implementasi Mobilitas Cerdas dalam Ekosistem Kota Cerdas: Analisis Kelembagaan dan Kebijakan Singapura dan Jakarta - Wahyu Purnama; Muhammad Dzakwannur Ghozy; Sri Sulistina; Ahmad Jeri Adam; Mansur Mansur; Enos Paselle (Universitas Medan Area, 2026)
This study is motivated by a research gap: prior studies have generally examined Singapore and Jakarta separately as single case studies or compared them descriptively without an explicit, measurable institutional-policy analytical framework for smart mobility. The novelty of this study lies in applying a comparative institutional and policy analysis framework that symmetrically integrates three smart mobility measurement dimensions less mobility, move freely, and less travel time across two cities with contrasting governance maturity. The study draws on collaborative governance theory, new institutionalism, the digital governance evolution framework, and instrument taxonomy as its main analytical lenses. It employs a descriptive qualitative comparative case study design, with a literature search and selection procedure adapted from the PRISMA flow, analyzed through Braun and Clarke's six-phase thematic analysis technique using a deductive coding matrix built on four variables: institutional structure, mobility integration performance, technological and payment innovation, and external regulation. Data trustworthiness was maintained through four criteria. Theoretically, this study contributes to the smart mobility governance literature by extending the three-dimension measurement framework to a cross-country comparative context, while enriching the Public Administration discipline's understanding of the interaction between institutional structure, public policy, and technology adoption. In terms of policy implications, the findings recommend strengthening inter-agency harmonization, accelerating fleet electrification, and formulating price-based policy instruments (electronic road pricing) that account for social equity for DKI Jakarta.